91.3k views
4 votes
Simplify f+g / f-g when f(x)= x-6 / x+7 and g(x)= x-7 / x+6

Simplify f+g / f-g when f(x)= x-6 / x+7 and g(x)= x-7 / x+6-example-1
User Liliane
by
6.3k points

2 Answers

4 votes

Answer:

C. 2x^2 - 85 / 13


User Intellidiot
by
6.2k points
6 votes
ANSWER


(f + g)/(f - g) = \frac{2 {x}^(2) - 85 }{ 13}

Step-by-step explanation

The given functions are


f(x) = (x - 6)/(x + 7)

and


g(x) = (x - 7)/(x + 6)

We are required to simplify,


(f + g)/(f - g)

We proceed as follows:


(f + g)/(f - g) = (f (x)+ g(x))/(f(x) - g(x))


(f + g)/(f - g) = ( (x - 6)/(x + 7) + (x - 7)/(x + 6))/((x - 6)/(x + 7) - (x - 7)/(x + 6))

This gives us,


(f + g)/(f - g) = ( ((x - 6)(x + 6) + (x + 7)(x - 7))/((x + 7)(x + 6)) )/(((x - 6)(x + 6) - (x + 7)(x - 7))/((x + 7)(x + 6)) )

This simplifies to,


(f + g)/(f - g) = ((x + 6)(x - 6) + (x + 7)(x - 7)/((x - 6)(x + 6) - (x - 7)x + 7))

We now apply difference of two squares to get,


(f + g)/(f - g) = \frac{ {x}^(2) - 36 + {x}^(2) - 49}{ {x}^(2) - 36- ( {x}^(2) - 49)}


(f + g)/(f - g) = \frac{ {x}^(2) - 36 + {x}^(2) - 49}{ {x}^(2) - 36- {x}^(2) + 49}

This further simplifies to,


(f + g)/(f - g) = \frac{2 {x}^(2) - 85 }{ 13}

Therefore the correct answer is C
User Ilia  Grabko
by
6.1k points